If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -3x + 5 = 4x + 5 Reorder the terms: 5 + -1x + -3x = 4x + 5 Combine like terms: -1x + -3x = -4x 5 + -4x = 4x + 5 Reorder the terms: 5 + -4x = 5 + 4x Add '-5' to each side of the equation. 5 + -5 + -4x = 5 + -5 + 4x Combine like terms: 5 + -5 = 0 0 + -4x = 5 + -5 + 4x -4x = 5 + -5 + 4x Combine like terms: 5 + -5 = 0 -4x = 0 + 4x -4x = 4x Solving -4x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4x + -4x = 4x + -4x Combine like terms: -4x + -4x = -8x -8x = 4x + -4x Combine like terms: 4x + -4x = 0 -8x = 0 Divide each side by '-8'. x = 0 Simplifying x = 0
| 2x+4/2x+3 | | 18x^2-48x-50=0 | | 10+-1=25 | | 8+3n=4n+2 | | X^3-18=9x-2x^2 | | -5=-14+7 | | a/4-7=10 | | 3x-3(-4x+12)=9 | | -9a^9+(-7a^9-5)= | | x^2+71=-18x-9 | | 2/2-x=x+1/1-x | | 13(-2)-4y=-66 | | 3x+2.1=0 | | 8x+4-7x=8-22 | | 4x^2-64x=192 | | 2*3(9y+3)=4y+7 | | 3k-9=6-2k | | x^2+9x+18=x+3 | | f(x)=5x^2-30x+49 | | -3(5y+6)-2(4y-4)-9y= | | 5(x-4)=4(x-3) | | 2(4x^2+2)=0 | | 40x-40=x+8 | | 4*x+2=-6 | | 5(y+2)+3(y-4)=0 | | 20-2y=4+0.5y | | 3x^2+30x+12=0 | | 7*h=-51 | | (5x)=(3x+13) | | -3.3(y+8)-2.5y= | | -9=9(h-2) | | 3x^2+30x-12=0 |